PEER RELATIONSHIPS, STUDENT LEARNING ENVIRONMENT AT HOME AND INDEPENDENCE OF LEARNING WITH LEARNING OUTCOMES SMP MUHAMMADIYAH 9 YOGYAKARTA - Isnaini Susilaningsih; Harina Fitriyani (Universitas Ahmad Dahlan, 2017)
Mathematics is still considered difficult by most students, so the impact on learning outcomes. The lack of good peers and learning environment that is less than adequate and conducive and the lack of seriousness and independent learning is some of the factors that may affect student learning. Therefore, this study was conducted in order to determine whether or not a positive and significant between peer relationships, student learning environment at home and independence of learning with learning outcomes in SMP Muhammadiyah 9 Yogyakarta in Academic Year 2016/2017. The population of this research was all students of class VIII of even semester in SMP Muhammadiyah 9 Yogyakarta in Academic Year 2016/2017 which consists of 5 classes. As a sample class was class VIII B by random sampling technique to class. The questionnaire technique used collection data peer relationships, student learning environment at home and learning independence, as well as the test technique used collection data mathematics learning result of student. Test instruments used validity, distinguishing features and reliability. Test data analysis requirements using the test for normality, independent, and the test for linearity. Data analysis for hypothesis testing using correlation analysis and linear regression analysis. The research result showed that there was a significant positive correlation between peer relationships, student learning environment at home and independence of learning with learning outcomes with and so that . Multiple correlation coefficient (R2) with a regression equation with relative contribution of ( ) = 14%, ( ) = 70%, ( ) = 16%, and effective contribution , , dan .